Pathways to nonprofit excellence - Light, Paul Charles (Brookings Institution Press, 2002)
Fourth in a series of reports on the changing nature of public service in government and the nonprofit sector, Pathways to Excellence focuses on a unique survey of contemporary thinking about creating effective nonprofit organizations. Based on interviews with 250 leading thinkers from the worlds of philanthropy, scholarship, and consulting, as well as 250 executive directors of some of the nation's most effective nonprofits, the book argues that there is no one best way to higher performance. Although higher performance clearly requires a commitment to excellence, it can be achieved along more than one pathway using one of several different strategies. Pathways to Excellence shows that every nonprofit organization can improve-no matter how well or poorly it is currently performing-often by taking simple first steps up a development spiral to high performance.
Keywords: Nonprofit organizations -- Management.; Organizational effectiveness.; Leadership.; Associations sans but lucratif -- Gestion.; Efficacité organisationnelle.; BUSINESS & ECONOMICS -- Nonprofit Organizations & Charities.; POLITICAL SCIENCE -- NGOs (Non-Governmental Organizations); Leadership; Nonprofit organizations -- Management; Organizational effectiveness